PENERAPAN TEPID WATER SPONGE DENGAN MASALAH HIPERTERMI PADA AN. M USIA 5 TAHUN AKIBAT DENGUE HEMORRAGIC FEVER (DHF) DERAJAT II DI RUANGAN MELATI RUMAH SAKIT TK.II DUSTIRA TANGGAL 16-18 MEI 2023 - Ningrum, Putri Zulfa Novia; Zulva, Siti (Jurnal Kesehatan An-Nuur, 2024)
Dengue Hemorragic Fever (DHF) is a viral disease transmitted by mosquitoesThe house of Egypt. (DHF) reported (WHO) increased from 505,430 cases in 2000, to 5.2 million cases in 2019. DHF can attack all ages, children aged ≤8.5 years are more susceptible to experiencing the risk of bleeding resulting from dengue infection with One of the symptoms that arise is hyperthermia. Givingtepid water sponge can be done for 15-20 minutes in one run with a water temperature of 37ºC (Team of Pokja Guidelines for SPO DPP PPNI, 2021). Givingtepid water sponge more effective in lowering the child's body temperature, this is due to the wiping technique on the body which will accelerate the vasodilation of peripheral blood vessels throughout the body so that the evaporation of heat from the skin to the surrounding environment will be faster. Results of An.M on the first day with hyperthermia nursing problems in implementing therapytepid water sponge 1 time for 15-20 minutes, with the result that the child has no fever anymore with an initial temperature of 38°C after compressingtepid water sponge there was a decrease to 36.7 °C (1.3°C), and these results are consistent with research results (Putri, et al, 2020). The purpose of the tepid water sponge compress is to help release body heat by means of convection which helps lower body temperature faster. Suggestions for the Community can understand compresstepid water sponge when a child has a fever, the author suggests that educational institutions implement therapeutic measurestepid water sponge. Suggestions for the next author can be used as professional and comprehensive nursing care data.